2008
DOI: 10.1021/ma802322j
|View full text |Cite
|
Sign up to set email alerts
|

Toward Tailorable Porous Organic Polymer Networks: A High-Temperature Dynamic Polymerization Scheme Based on Aromatic Nitriles

Abstract: Triazine-based polymer scaffolds with controllable porosity were prepared through a dynamic polymerization scheme based on a broad variety of aromatic nitriles, upon polytrimerization of the latter from ZnCl 2 salt melts at high temperatures. In the present study, the reaction parameters such as the temperature and monomer concentration as well as the geometry and functionality of the monomers were systematically varied. A comprehensive overview of the influences of these parameters on the outcome of the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
302
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(321 citation statements)
references
References 38 publications
12
302
1
4
Order By: Relevance
“…Its poresize distribution confirmed the existence of micropores of ca.1.4 nm (Fig. 1a), which was observed by previous reports [29][30][31] ( Fig. 2b).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Its poresize distribution confirmed the existence of micropores of ca.1.4 nm (Fig. 1a), which was observed by previous reports [29][30][31] ( Fig. 2b).…”
Section: Resultssupporting
confidence: 87%
“…S2) gives a further details about the BPOE: This framework is formed as a short-range-ordered 2D structure with the stacking of each 2D unit (Fig. 1a) in a noncoplanar fashion [29][30][31] as the global structure. Raman spectroscopy measurements (RSMs) allow to reveal the electronic structure of materials ( ¼ information about a structural periodicity of a material) [32][33][34] .…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the abundance of metal bipy complexes known and the versatility of the bipy ligand in homogeneous catalysis, a CTF framework based on this ubiquitous type of ligand may ultimately provide a link between a homogeneous catalyst and its heterogeneous counterpart, both featuring a metal bipy unit as the catalytically active site. First attempts to synthesize a bipy CTF have been made by Kuhn et al recently, 14 yet the resulting amorphous powders were reported to possess no apparent porosity and a surface area of essentially zero. In the present paper we demonstrate the synthesis of a highly porous bipy CTF and give a detailed account of the complex interplay between local and long range order, porosity, and nitrogen content to enable a deeper under standing of the structure and a more rational approach to the design of covalent triazine frameworks.…”
Section: 23mentioning
confidence: 99%
“…This behavior is attributed to the consumption of the monomer during the reactions. The peaks at 1523 and 1351 cm -1 in KPOP-6a and KPOP-6b's spectra confirm the formation of triazine rings 11,[35][36][37] while the very weak intensity of the corresponding peaks in the spectra of KPOP-6c, KPOP-6d, and KPOP-6e is indicative of the triazine decomposition. …”
mentioning
confidence: 97%